2011
DOI: 10.1007/s10641-011-9951-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and substrate on the development of the cortisol stress response in the lake sturgeon, Acipenser fulvescens, Rafinesque (1817)

Abstract: Lake sturgeon, Acipenser fulvescens, are considered threatened or endangered throughout most of their North American Range. Current hatchery rearing for re-stocking programs utilise conventional methods with little to no understanding of the relationship between rearing conditions and the development of the hypothalamic-pituitary-interrenal (HPI) stress axis. In the present study we examined the effects of substrate type and temperature on the development of the HPI stress axis in prolarval and larval lake stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
1
15
1
3
Order By: Relevance
“…Here we determined that white sturgeon larval growth and condition factor, gut development, U crit , SRRT, and FA composition were all altered when reared in the absence of enriched substrates, although temperature and parentage in some cases mediated or exacerbated those effects. The identification of more phenotypic limitations associated with poor substrate conditions in sturgeon provides further support (see also Gessner et al., ; Zubair et al., ; Boucher et al., ) for the causal links between reduced substrate complexity (i.e. loss of interstitial habitats) and recruitment limitations (McAdam et al., ; Paragamian et al., ; McAdam, ).…”
Section: Discussionmentioning
confidence: 86%
“…Here we determined that white sturgeon larval growth and condition factor, gut development, U crit , SRRT, and FA composition were all altered when reared in the absence of enriched substrates, although temperature and parentage in some cases mediated or exacerbated those effects. The identification of more phenotypic limitations associated with poor substrate conditions in sturgeon provides further support (see also Gessner et al., ; Zubair et al., ; Boucher et al., ) for the causal links between reduced substrate complexity (i.e. loss of interstitial habitats) and recruitment limitations (McAdam et al., ; Paragamian et al., ; McAdam, ).…”
Section: Discussionmentioning
confidence: 86%
“…For example, Stelzer et al (2008) analyzed the gut content of lake sturgeon in Lake Winnebago and found that gizzard shad (Dorosoma cepedianum) and Chironomus plumosus larvae comprise 56% and 33% of gut content mass, respectively, which was confirmed with a mixing model using ␦ 13 C and ␦ 15 N. Additionally, a study by Anderson et al (2012) and Choudhury et al (1996) confirmed the importance of Chironomidae in the Lake Winnebago diet and found that the chironomids were in high enough abundance to support the sturgeon. A diet study conducted by Volkman et al (2004) on juvenile lake sturgeon in hatcheries found that blood worms (Chironomus spp.)…”
Section: Dietmentioning
confidence: 83%
“…Similar studies conducted on the physical rearing environment reveal equally significant information. Zubair et al (2012) conducted experiments demonstrating that temperature has a significant impact on the development of the cortisol stress responses in lake sturgeon, which can lead to stressrelated issues. Similarly, Wang et al (1985) underscore the importance of temperature, stating that optimal survival for rearing of offspring is 14-17°C with mortalities occurring at temperatures higher than 20°C.…”
Section: Stocking Programsmentioning
confidence: 99%
“…The duration of yolk-sac utilization until the timing of emergence from the substrate when larvae disperse downstream to begin exogenously feeding is dependent on several abiotic conditions within larval rearing sites including temperature (Duong et al, 2011). Rearing temperatures prior to exogenous feeding are known to influence the cortisol response and induce thermal stress in larval lake sturgeon (Zubair, Peake, Hare, & Anderson, 2012).…”
mentioning
confidence: 99%